A new fatigue damage accumulation rating life model of ball bearings under vibration load. Issue 10 (1st June 2020) - Cui, Li
Abstract : Purpose: Bearings in electric machines often work in high speed, light load and vibration load conditions. The purpose of this paper is to find a new fatigue damage accumulation rating life model of ball bearings, which is expected for calculating fatigue life of ball bearings more accurately under vibration load, especially in high speed and light load conditions. Design/methodology/approach: A new fatigue damage accumulation rating life model of ball bearings considering time-varying vibration load is proposed. Vibration equations of rotor-bearing system are constructed and solved by Runge–Kutta method. The modified rating life and modified reference rating life model under vibration load is also proposed. Contrast of the three fatigue life models and the influence of dynamic balance level, rotating speed, preload of ball bearings on bearing's fatigue life are analyzed. Findings: To calculate fatigue rating life of ball bearings more accurately under vibration load, especially in high speed and light load conditions, the fatigue damage accumulation rating life model should be considered. The optimum preload has an obvious influence on fatigue rating life. Originality/value: This paper used analytical method and model that is helpful for design of steel ball bearing in high speed, light load and vibration load conditions. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-05-2019-0180/